Red Flag And Auditor Experience Toward Criminal Detection Trough Profesional Skepticism - Syamsuri Rahim; Muslim Muslim; Asbi Amin (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This research was conducted to examine the influence of red flags variables, auditor work experience and professional auditor skepticism on fraud detection. The test is to seek the influence of red flags variables and work experience on professional auditor skepticism. And the test of the red flag variables and auditor work experience on fraud detection through professional auditor skepticism. The number of samples used was 40 people from 8 Public Accountant offices in Makassar City using the census method. Data collection research uses questionnaires in the form of questionnaires. The data analysis technique used is the Partial Least Square (PLS) Method. The results showed that the red flags and professional skepticism had a positive and significant influence on fraud detection, while the auditor's work experience had a positive but not significant influence on fraud detection. Red flag and auditor work experience have a positive and significant influence on professional skepticism. Professional skepticism is able to mediate the significant influence between red flags and auditor work experience on fraud detection.